Peran Public Speaking dalam Mengembangkan Keterampilan Komunikasi Siswa di SDN Panglegur 2 - Zahra, Khotimatus; Feni Aprilia; Nufila Abida; Noer Rahmatul Laila (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2025)
This study aims to determine the role of public speaking in developing students' communication skills at SDN Panglegur 2. Public speaking is one of the effective learning methods in improving public speaking skills, courage to express opinions, and building students' self-confidence from an early age. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the implementation of structured public speaking activities, such as class presentations, storytelling, and short speeches, can significantly improve students' verbal communication skills. In addition, students become more active in discussions, are able to convey ideas clearly, and show an increase in the use of effective language. These findings indicate that public speaking has an important role in the learning process and development of students' interpersonal communication at the elementary school level. Therefore, it is recommended that public speaking activities be integrated continuously into the learning curriculum.